Positive Association Between Aggressive Driving and Work Stress Among Female Drivers: Terdapat Hubungan Positif Antara Perilaku Mengemudi Agresif dan Stres Kerja di Kalangan Pengemudi Wanita - Naufal Edriansah Purnomo; Widyastuti (Academia Open, 2025)
General Background: Aggressive driving and occupational stress represent complex behavioral and psychological concerns that may threaten driver safety and road user security. Specific Background: Female online motorbike taxi drivers operate in dynamic urban environments that require continuous interaction with traffic demands and service expectations. Knowledge Gap: Empirical evidence examining the statistical relationship between aggressive driving behavior and occupational stress among female online motorbike taxi drivers in Surabaya remains limited. Aims: This study aimed to examine the correlation between aggressive driving and occupational stress among female online motorbike taxi drivers in Surabaya. Results: This quantitative correlational study involved 100 respondents selected through simple random sampling. Measurement utilized validated occupational stress (R=0.920) and aggressive driving scales (R=0.887). Pearson correlation and linear regression analysis using JASP version 0.18.1.0 indicated a statistically significant positive relationship with p < .001. Descriptive analysis showed relatively low levels of both variables among respondents, potentially related to flexible working schedules, social support, and application-based operational assistance. Novelty: This study provides quantitative evidence focusing specifically on female online motorbike taxi drivers in Surabaya using validated behavioral and psychological measurement instruments. Implications: The findings contribute to occupational psychology and transportation safety discussions by highlighting the relationship between driving behavior patterns and psychological working conditions within app-based transportation services. Highlights: Statistical Testing Revealed Significance With P-Value Below 0.001. Respondents Demonstrated Relatively Low Behavioral and Psychological Score Averages. Flexible Scheduling and Social Support Were Associated With Reduced Behavioral Risk Tendencies. Keywords: Aggressive Driving, Occupational Stress, Online Motorbike Taxi Drivers, Transportation Safety; Occupational Psychology